IMPLEMENTASI BAHAN AJAR MEDIA AUTOPLAY STUDIO 8 MATERI MOTIF BATU NISAN DI KESULTANAN PALEMBANG DARUSSALAM - Syarifuddin Syarifuddin; Maura Rizki Amelia; Hudaidah Hudaidah (Akademika : Jurnal Teknologi Pendidikan, 2022)
This research on the development of the motifs of the Palembang Darussalam sultanate tombstones tries to provide effective learning outcomes. The method used is quantitative using the Borg and Gall models to research and develop prototypes. The subject of this research is the students of class X SMA N 1 Palembang. The product has gone through a one-on-one expert revision stage carried out by 3 experts with attached comments so that this learning teaching material product is considered very valid with an average score of 4.67. The effectiveness of learning teaching materials using Autoplay Studio 8 which has been developed and carried out in the test phase, the results of the trial got a score of 46.2% with the n-gain value reaching a score of 0.72. This means that the prototype is suitable for use as an effective learning tool for class X SMA N 1 Palembang and as a learning support product